CLARIN : The Infrastructure for Language Resources - Darja Fišer; Andreas Witt (De Gruyter, 2022)
CLARIN, the'Common Language Resources and Technology Infrastructure', has established itself as a major player in the field of research infrastructures for the humanities. This volume provides a comprehensive overview of the organization, its members, its goals and its functioning, as well as of the tools and resources hosted by the infrastructure. The many contributors representing various fields, from computer science to law to psychology, analyse a wide range of topics, such as the technology behind the CLARIN infrastructure, the use of CLARIN resources in diverse research projects, the achievements of selected national CLARIN consortia, and the challenges that CLARIN has faced and will face in the future. The book will be published in 2022, 10 years after the establishment of CLARIN as a European Research Infrastructure Consortium by the European Commission (Decision 2012/136/EU). Watch our book talk with the editors Darja Fišer and Andreas Witt here: https://youtu.be/ZOoiGbmMbxI